Performance Appraisal for Career Development in A Semi-Political Institution - Eko Prasojo; Ghina Samarah; Desy Hariyati (Universitas Sultan Ageng Tirtayasa, 2023)
Abstract: Performance management has become a popular instrument of reform in many countries and effectively improves the quality of bureaucracy. Its use is not limited to the macro and meso-levels but extends to the micro level as a basis for individual career development. Objectivity and subjectivity are contradictory but appear simultaneously in performance appraisal practice. This paper focuses on performance appraisal practices for individual career development in a semi-political organization in terms of four aspects: education, training, promotion, and rotation. The study uses a qualitative method to gather primary data through interviews with source persons in the Secretariat General of the House of Representatives, Republic of Indonesia. The result shows that subjectivity and political factor dominate employees’ performance appraisal as well as career development. It occurs predominantly in the process of rotation and promotion. Furthermore, performance appraisals have not been used in creating an individual development plan in terms of education and training.